Manajemen Transformasi Digital Pembayaran: Faktor-Faktor Adopsi E-Money dan Implikasinya pada Velocity of Money - Alfitri Ramadhani; Dewa Putu Yudi Pardita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The transformation of digital payments has significantly reshaped Indonesia's monetary landscape, primarily through the widespread adoption of electronic money (e-money). This study investigates the relationship between e-money adoption and the velocity of money using comprehensive secondary time-series data from 2020 to 2024. An econometric approach was employed, utilizing data from Bank Indonesia, Statistics Indonesia (BPS), and industry reports. The findings reveal a strong negative correlation (-0.847) between e-money transaction volume and M1 velocity, indicating fundamental shifts in monetary circulation patterns. E-money transactions grew from 5.2 billion in 2020 to 13.76 billion in the first eight months of 2024 (CAGR: 27.4%), while M1 velocity decreased from 13.16 to 12.1. Granger causality testing confirms that e-money adoption significantly affects the velocity of money with a one-quarter lag. The study offers strategic policy recommendations for adapting monetary frameworks and optimizing the digital payment ecosystem. These findings provide important macroeconomic insights and can inform central bank strategies in emerging economies.